2023
DOI: 10.1029/2022jb025868
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Changes in Gas Transport and Sediment Stiffness Influenced by Regional Stress: Observations From Piezometer Data Along Vestnesa Ridge, Eastern Fram Strait

Abstract: Fine-grained marine sediments along continental slopes and rises are saturated with gas rich fluids. The mechanisms of gas transport from the source toward the seafloor influence the sediment geomechanical properties as well as gas hydrate accumulations and seepage dynamics (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 94 publications
(212 reference statements)
2
5
0
Order By: Relevance
“…To tie the metric core records to the time records of the Chirp data, the core records were converted to time using an average seismic velocity of 1,500 m/s, which was found suitable based on the sediment content and GEOTEK measurements (Magnetic susceptibility, wet bulk density, P-wave velocity and impedance; Supplementary Figure S6). The same average seismic velocity for the upper sediment column at Vestnesa Ridge was observed by other studies (e.g., Plaza-Faverola et al, 2023). CTD measurements have shown that sound velocity in the water column is on average 1,465 m/s in our study area (Figures 2A,C,D).…”
Section: Shallow Seismic Datasupporting
confidence: 90%
“…To tie the metric core records to the time records of the Chirp data, the core records were converted to time using an average seismic velocity of 1,500 m/s, which was found suitable based on the sediment content and GEOTEK measurements (Magnetic susceptibility, wet bulk density, P-wave velocity and impedance; Supplementary Figure S6). The same average seismic velocity for the upper sediment column at Vestnesa Ridge was observed by other studies (e.g., Plaza-Faverola et al, 2023). CTD measurements have shown that sound velocity in the water column is on average 1,465 m/s in our study area (Figures 2A,C,D).…”
Section: Shallow Seismic Datasupporting
confidence: 90%
“…Nonetheless, even small fluctuations at the base of the GHSZ associated with the HS1 oceanic warming would have affected the already deformed sediments above the base of the GHSZ (Figure 9), as well as impacted near-surface sediments through further authigenic carbonate precipitation after gas hydrate dissolution and gas release (e.g., Sultan et al, 2020) (Figure 9). Additionally, as the system is critically stressed, small increases in free gas amounts beneath the base of the GHSZ would have been enough to trigger gas release through pre-existing fractures within the GHSZ along the Vestnesa Ridge (Ramachandran et al, 2022;Plaza-Faverola et al, 2023). This process reconciles the observation of small-scale buried pockmarks at highly deformed intervals (Figure 4, Figure 5, Figure 6).…”
Section: Gas Hydrate Dynamics During Glacial/ Interglacial Transitionssupporting
confidence: 52%
“…In response to environmental changes, the re‐equilibration of the old BGHSZ from BSR2 to its current position suggests a decomposition of GH in a mixture of free gas and dissolved gas in the GH destabilization zone (GHDZ) (Sultan, 2007) (Figures 5(5)). Experimental studies show that grain size and connectivity between micro‐structures of the host sediment determine how gas is transported toward the surface (Jain & Juanes, 2009; Plaza‐Faverola et al., 2023). In the study zone, the very low permeability of the host sediment containing high amounts of clay‐silt (Ballas et al., 2018; Riedel et al., 2020) suggests that the fluid flow regime induced by hydrate dynamics is dominated by a gas diffusion process.…”
Section: Discussionmentioning
confidence: 99%